2021
DOI: 10.1111/cge.14074
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and metabolic profiling of individuals with Phelan‐McDermid syndrome presenting with seizures

Abstract: Phelan-McDermid syndrome (PMS) (OMIM*606232) is a rare genetic disorder characterized by intellectual disability, autistic features, speech delay, minor dysmorphia, and seizures. This study was conducted to investigate the prevalence of seizures and the association with genetic and metabolic features since there has been little research related to seizures in PMS. For 57 individuals, seizure data was collected from caregiver interviews, genetic data from existing cytogenetic records and Sanger sequencing for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…SHANK3 is a scaffolding protein of the postsynaptic density of glutamatergic synapses 11 , 12 , 13 ; additional disrupted genes within larger class II mutations have been implicated in processes related to stress and inflammation, mitochondrial function, neuronal differentiation, and cellular metabolism. 5 , 14 , 15 , 16 Molecular profiling of tissues derived from PMS participants, albeit scarce, confirm these functional categories and support the notion of unique molecular programs underlying distinct clinical subtypes. For example, increased severity of PMS phenotypes and larger 22q13.3 deletions have been associated with alterations in mitochondrial complex I and IV activity, 14 changes in peripheral blood epi-signatures enriched for neuronal development and intracellular signaling, 15 and metabolomic changes implicated in metabolic stress and response to cytokines regulating inflammation, 15 , 16 all poised to influence neurodevelopment.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…SHANK3 is a scaffolding protein of the postsynaptic density of glutamatergic synapses 11 , 12 , 13 ; additional disrupted genes within larger class II mutations have been implicated in processes related to stress and inflammation, mitochondrial function, neuronal differentiation, and cellular metabolism. 5 , 14 , 15 , 16 Molecular profiling of tissues derived from PMS participants, albeit scarce, confirm these functional categories and support the notion of unique molecular programs underlying distinct clinical subtypes. For example, increased severity of PMS phenotypes and larger 22q13.3 deletions have been associated with alterations in mitochondrial complex I and IV activity, 14 changes in peripheral blood epi-signatures enriched for neuronal development and intracellular signaling, 15 and metabolomic changes implicated in metabolic stress and response to cytokines regulating inflammation, 15 , 16 all poised to influence neurodevelopment.…”
Section: Introductionmentioning
confidence: 61%
“… 5 , 14 , 15 , 16 Molecular profiling of tissues derived from PMS participants, albeit scarce, confirm these functional categories and support the notion of unique molecular programs underlying distinct clinical subtypes. For example, increased severity of PMS phenotypes and larger 22q13.3 deletions have been associated with alterations in mitochondrial complex I and IV activity, 14 changes in peripheral blood epi-signatures enriched for neuronal development and intracellular signaling, 15 and metabolomic changes implicated in metabolic stress and response to cytokines regulating inflammation, 15 , 16 all poised to influence neurodevelopment. Notably, even transcriptomics of peripheral blood and postmortem brain tissue from participants with idiopathic ASD implicate changes related to inflammation, cellular proliferation/metabolism and immune dysfunction, 17 , 18 , 19 supporting the notion that ongoing dysregulation of the immune system echoes alterations in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 61%
“…There are three genes that are proposed as the main candidates for macrocephaly ( TBC1D22A , CELSR1 , and GRAMD4 ) given their location in the highly associated genomic regions, proposed function, or high probability of loss of function intolerance [ 71 ]. TBC1D22A has been associated with structural or functional abnormalities of the head or the central nervous system (CNS), such as seizures, schizophrenia, or bipolar disorder [ 72 , 73 ]. Boucherie et al (2018) found Celsr1-deficient mice to have microcephaly and cortical hypoplasia [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…SHANK3 is a scaffolding protein of the postsynaptic density of glutamatergic synapses [11][12][13] ; additional disrupted genes within larger Class II mutations have been implicated in processes related to stress and inflammation, mitochondrial function, neuronal differentiation, and cellular metabolism [14][15][16][17] . Molecular profiling of tissues derived from PMS participants, albeit scarce, confirm these functional categories and support the notion of unique molecular programs underlying distinct clinical subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular profiling of tissues derived from PMS participants, albeit scarce, confirm these functional categories and support the notion of unique molecular programs underlying distinct clinical subtypes. For example, increased severity of PMS phenotypes and larger 22q13.3 deletions have been associated with alterations in mitochondrial complex I and IV activity 15 , changes in peripheral blood epi-signatures enriched for neuronal development and intracellular signaling 16 , and metabolomic changes implicated in metabolic stress and response to cytokines regulating inflammation [16][17] , all poised to influence neurodevelopment. Notably, even transcriptomics of peripheral blood and postmortem brain tissue from participants with idiopathic ASD implicate changes related to inflammation, cellular proliferation/metabolism and immune dysfunction [18][19][20] , supporting the notion that ongoing dysregulation of the immune system echoes alterations in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%